Interpersonal meaning analysis of Freddie Dredd selected songs in "Suffer" album - Ananda, Satria; Purbasari, Rahayu (Lililacs Journal, 2022)
This study aims to analyze the interpersonal meaning in five selected song lyrics from Freddie Dredd’ s album to describe the interpersonal meaning elements namely mood and modality. Then, the study also uses lexical analysis to analyze the attitudinal elements in the song lyrics. This research uses descriptive qualitative approach. The data is contained by separating the lyrics into clauses. Then, the data is analyzed by using two major instruments namely interpersonal meaning which analyzes the mood types and the modality. Then, the study uses appraisal system to realize the attitude of the speaker. In interpersonal meaning analysis, the most dominant mood type is declarative mood with the total of 132 clauses from 162 clauses or about 81.48% and the most modality found is median modality with 9 occurrences or about 50% from total of 18. In attitudinal appraisal analysis, the most dominant attitude element is Judgement (83.33%), followed by Affect (13.34%) and Appreciation (3.33).